2006
DOI: 10.1152/ajpheart.00768.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-dose oral vitamin C partially replenishes vitamin C levels in patients with Type 2 diabetes and low vitamin C levels but does not improve endothelial dysfunction or insulin resistance

Abstract: Endothelial dysfunction is a hallmark of Type 2 diabetes related to hyperglycemia and oxidative stress. Nitric oxide-dependent vasodilator actions of insulin may augment glucose disposal. Thus endothelial dysfunction may worsen insulin resistance. Intra-arterial administration of vitamin C improves endothelial dysfunction in diabetes. In the present study, we investigated effects of high-dose oral vitamin C to alter endothelial dysfunction and insulin resistance in Type 2 diabetes. Plasma vitamin C levels in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 86 publications
4
107
1
1
Order By: Relevance
“…Importantly, there was no improvement in forearm vascular responses to the endothelium-independent vasodilator sodium nitroprusside, which suggests that the beneficial effects of fruit and vegetable intake are related to protective effects on the endothelium 156 . The data from this study are in contrast to forearm plethysmography studies that assessed the effect of ascorbic acid on forearm vascular responses and suggest that a balanced, pragmatic approach that considers whole food and dietary patterns may be the best means of improving the overall vascular phenotype of patients with hypertension 156,[178][179][180] . Increased fruit and vegetable consumption may also make patients more likely to adopt other favourable dietary modifications, such as reduced salt and fat consumption.…”
mentioning
confidence: 59%
“…Importantly, there was no improvement in forearm vascular responses to the endothelium-independent vasodilator sodium nitroprusside, which suggests that the beneficial effects of fruit and vegetable intake are related to protective effects on the endothelium 156 . The data from this study are in contrast to forearm plethysmography studies that assessed the effect of ascorbic acid on forearm vascular responses and suggest that a balanced, pragmatic approach that considers whole food and dietary patterns may be the best means of improving the overall vascular phenotype of patients with hypertension 156,[178][179][180] . Increased fruit and vegetable consumption may also make patients more likely to adopt other favourable dietary modifications, such as reduced salt and fat consumption.…”
mentioning
confidence: 59%
“…Therefore, we were unable to address whether the low serum levels and the coexistence of DM was a cause of the disease or the consequence, while the studies by Harding et al (20) show the evident causal relationship of vitamin C in the development of DM. However, it is controversial whether a high oral dose of vitamin C is beneficial in persons with DM (41)(42)(43)(44)(45) or preventing DM (46). Besides the protective effect of a high dose, it may be necessary to study whether low or deficient status of vitamin C leads or accelerates the development of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C at higher doses than those used to compound BH 4 has been demonstrated in some studies to have a mild antihypertensive effect 26 and to improve endothelial function, although this remains a subject of controversy. [27][28][29][30] To overcome this possibility, we made baseline measurements after a 2-week run-in period with vitamin C alone in Study 2 and found no change in BP. However, a synergistic effect of vitamin C with BH 4 cannot be excluded.…”
Section: Study Limitationsmentioning
confidence: 99%